Trends and research features on ecosystem services of agroforestry system: bibliometric review - Chaffra Charles, Yabi; Séverin , Biaou; Enagnon Benoit Olivier, Ahouandjinou; Nounagnon Gérard , Gouwakinnou (Revue Ecosystèmes et Paysages, 2024)
Tropical agroforestry systems make an important contribution to mitigating the effects of climate change and conserving biodiversity. Despite the scientific gaps regarding the ecosystem services of these particular ecosystems, understanding how tropical agroforestry systems work is essential if we are to take full advantage of the ecosystem services they provide. Although there has been a boom in the study of the ecosystem services provided by agroforestry systems, few syntheses are structuring this knowledge in the context of the challenges posed by climate change. This study aims to analyse global trends in agroforestry-related ecosystem services and their implications for climate change mitigation based on a bibliometric analysis of 1965 articles published between 1992 and 2022 and extracted from the Scopus database. These extracted data were analysed using the Biobliometrix R tool to examine sources, authors and documents. The results reveal a notable increase in interest in agroforestry’s ecosystem services, coupled with a rise in international collaborations, especially among African countries, Germany, and France. These partnerships reflect a shared commitment to understanding agroforestry systems and developing sustainable solutions. Furthermore, our analysis identifies key research themes, guiding future studies. Ecosystem services, climate dynamics, and biodiversity emerge as central aspects of agroforestry research. The findings highlight agroforestry’s multiple benefits, particularly its role in adapting to and mitigating climate change while significantly contributing to biodiversity conservation. A thorough evaluation of agroforestry systems is, therefore, crucial to developing innovative, integrated strategies that address current environmental and climate challenges.